Research progress and current applications of nutrient profiling systems domestically and internationally - Zhuo SUN; Jiangyue YU; Qi SONG; Shupeng MAI; Zhengyuan WANG; Jiajie ZANG (Zhongguo gonggong weisheng)
Nutrient profiling systems (NPS) are scientific methods that classify or rank foods based on their nutrient composition and apply algorithms to the field of nutrition and health to help consumers make healthy food choices. The research and application of NPS play a critical role in improving the nutritional literacy of citizens and promoting healthy food choices, so it is essential to scientifically validate newly developed NPS models. Currently, there are more than 100 NPS models worldwide, of which threshold-based NPS models are widely used in front-of-package labelling, food advertising restrictions, and internal food company ratings. This article provides an overview of the research and application status of NPS both domestically and internationally. It also presents the construction and validation methods of NPS models, as well as the attitudes and perspectives of various stakeholders towards NPS.